Occupations as housing models: The everyday and political role of collective labour in sustaining an occupation over time - Fortuin, Kezia (Department of Environmental and Geographical Science, 2025)
In line with calls to decolonise planning, and planning imaginaries, this dissertation takes seriously one of the most pervasive models of securing housing and connecting to basic services across the global south: the occupation of land and buildings. Emerging literature has established the everyday labour of survival in occupations as equally a political labour, disrupting earlier understandings of occupations as either survival strategy or political statement. Enquiring into occupations as existing models of housing provisioning, this dissertation uses the notion of ‘labour' to understand how occupations are sustained over time at their everyday and political scales. The research is informed by two years of ad-hoc engagements with, and five months of focused ethnographic fieldwork at, the Cissie Gool House building occupation in Cape Town. Limiting the study to four of the occupation's spaces of collective labour – the kitchen, the garden, the maintenance team and the security and safety team – the research finds an established system of resident-led management guided by mature strategies to respond to crisis, keep the community safe, counter criminalisation and meet community needs. Moreover, in the context of state dis-engagement and the threat of eviction, their model of resident-led management has become crucial evidence of their capacity to be engaged. This evidence is mobilised in the effort to ‘reach for the state' in the carving out of the future of the site as affordable housing. ‘Labour,' although understudied in the infrastructural turn, is useful empirically, in providing an attentive, intimate and embodied reading of southern urban planning and repair practices; conceptually, in tying together disparate bodies of literature on southern urbanism, infrastructures, repair and affect; and methodologically, in insisting on the use of the body to generate data. As such, I advocate for an embodied turn in the study of southern urban planning and repair practices.